Contamination With Fumonisin B and Deoxynivalenol Is a Threat to Egg Safety and Contributes to Gizzard Ulcerations of Newborn Chickens - Wang, Yihui; Quan, Hongkun; Li, Xiaohui; Li, Qiang; Haque, Md Atiqul; Shi, Qin; Fu, Qiang; He, Cheng (Frontiers in Microbiology, 2021)
Fumonisin B (FB) and other fumonisins, deoxynivalenol (DON), and zearalenone (ZEN) are mycotoxins (secondary metabolites of fungi) present at high levels of contamination in poultry diets and threatening the sustainability of the poultry industry and egg safety for consumers. However, residual mycotoxins in breeder eggs and their effects on chicken progeny and gizzard ulcerations remain unclear. To unveil mycotoxin contaminations from daily diets to breeder eggs, 293 poultry feed samples were collected from three large-scale poultry provinces across Northern China to Southern China. Average levels of 1,628 ± 4.36 μg/kg of FB1, 593 ± 11.16 μg/kg of DON, 69 ± 9.21 μg/kg of ZEN, 52 ± 7.33 μg/kg of OTA, and 24 ± 5.85 μg/kg of AFB1 were found in feedstuffs and poultry diets using commercial ELISA kits. In terms of residual mycotoxins in breeder eggs, FB1 and DON contaminations dominated residues in egg albumen and yolk samples. Out of 221 breeder eggs, the average residual of FB1 in albumen were 320.6 ± 10.12 μg/kg (Hebei), 420.2 ± 10.98 μg/kg (Guangdong), and 549.4 ± 10.27 (Guangxi). Moreover, higher residual of DONs were determined in Guangdong and Guangxi provinces compared to Hebei province. ZEN, ochratoxins A (OTA), and aflatoxin B1 (AFB1) contamination at low levels were found in the above samples collected from afronmentioned three provinces. Based on residual mycotoxins in breeder eggs, SPF embryonated eggs aged 11 days were inoculated into albumen with different doses of FB1, FB2 or DON, or a combination of FB1 and DON, or a combination of FB1 with FB2 and FB3. A lower hatching rate was observed in the chicken progenies with the combination of 24 μg of FB1 and 0.1 μg of DON compared to other treatments. Moreover, typical gizzard ulcerations with hemorrhagic lungs were observed in the progeny of breeder eggs post-inoculation of 24 μg of FB1 and synergetic inoculation of FB1 and DON. Finally, residual FB mycotoxins were detected in the gizzards and in the lungs of the progenies. Based on the above evidence, feed-borne FB1 and DON are dominant mycotoxins in breeder eggs and threatening food security using breeder eggs as a Trojan horse. More importantly, the residual of FB1 alone and in combination with of DON contamination are associated with low hatching rate and gizzard ulcerations in chicken progenies, hampering sustainable development perspectives of the poultry industry.